2019
DOI: 10.1210/jc.2018-02025
|View full text |Cite
|
Sign up to set email alerts
|

Climacteric Status at the Age of 46: Impact on Metabolic Outcomes in Population-Based Study

Abstract: at the modification stage), and do not reflect editorial changes. No corrections/changes to the PDF manuscripts are accepted. Accordingly, there likely will be differences between the Advance Article manuscripts and the final, typeset articles. The manuscripts remain listed on the Advance Article page until the final, typeset articles are posted. At that point, the manuscripts are removed from the Advance Article page. DISCLAIMER: These manuscripts are provided "as is" without warranty of any kind, either expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…It is possible, however, that women ever using HRT have underlying hormonal differences from women never using HRT, which drive their need for HRT use. In accordance with the latter, women from the Northern Finland Birth Cohort 1966 experiencing earlier climacterium at age 46 years were more likely to use HRT and had fewer pregnancies but more metabolic disturbances, higher fat and lower muscle mass compared to pre-climacteric women at the same age, and additionally had lower testosterone levels even at age 31 years 39 . In our study, post-menopausal women with past or current HRT use had experienced menopause at a younger age compared to those never using HRT.…”
Section: Discussionmentioning
confidence: 53%
“…It is possible, however, that women ever using HRT have underlying hormonal differences from women never using HRT, which drive their need for HRT use. In accordance with the latter, women from the Northern Finland Birth Cohort 1966 experiencing earlier climacterium at age 46 years were more likely to use HRT and had fewer pregnancies but more metabolic disturbances, higher fat and lower muscle mass compared to pre-climacteric women at the same age, and additionally had lower testosterone levels even at age 31 years 39 . In our study, post-menopausal women with past or current HRT use had experienced menopause at a younger age compared to those never using HRT.…”
Section: Discussionmentioning
confidence: 53%
“…The duration of amenorrhea was less than 24 months for two-thirds of climacteric women, whose exact menstrual anamnesis was available. 39 A total of 76 of the climacteric women used HT. The background and clinical characteristics of climacteric and preclimacteric women at age 46 are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier study with this population found that earlieronset of the climacteric phase is associated with unfavorable changes in cardiovascular risk profile. 39 Studies have suggested that HT use might protect postmenopausal women against cardiovascular diseases. 50,51 In addition, some evidence suggests that adequate 25(OH)D concentrations may have an atheroprotective function.…”
Section: Discussionmentioning
confidence: 99%
“…This division has been described in detail in our earlier studies. 17,18 As there are no general criteria for climacterium, the European Society of Human Reproduction and Embryology (ESHRE) criteria for POI and Stages of Reproductive Aging Workshop (STRAW þ10) criteria for menopausal transition were applied. 4,21 The group of climacteric women included women in the late perimenopausal and postmenopausal stages with FSH !…”
Section: Study Groupsmentioning
confidence: 99%